Adaptive and degenerative evolution of the S-Phase Kinase-Associated Protein 1-Like family in Arabidopsis thaliana - Hua, Zhihua; Gao, Zhenyu (PeerJ, 2019)
Genome sequencing has uncovered tremendous sequence variation within and between species. In plants, in addition to large variations in genome size, a great deal of sequence polymorphism is also evident in several large multi-gene families, including those involved in the ubiquitin-26S proteasome protein degradation system. However, the biological function of this sequence variation is yet not clear. In this work, we explicitly demonstrated a single origin of retroposed Arabidopsis Skp1-Like (ASK) genes using an improved phylogenetic analysis. Taking advantage of the 1,001 genomes project, we here provide several lines of polymorphism evidence showing both adaptive and degenerative evolutionary processes in ASK genes. Yeast two-hybrid quantitative interaction assays further suggested that recent neutral changes in the ASK2 coding sequence weakened its interactions with some F-box proteins. The trend that highly polymorphic upstream regions of ASK1 yield high levels of expression implied negative expression regulation of ASK1 by an as-yet-unknown transcriptional suppression mechanism, which may contribute to the polymorphic roles of Skp1-CUL1-F-box complexes. Taken together, this study provides new evolutionary evidence to guide future functional genomic studies of SCF-mediated protein ubiquitylation.
Keywords: Arabidopsis Skp1-Like; Evolution; Adaptive; Degenerative; F-box; Protein–protein interaction; Selection; Polymorphism; Phylogenetics